Tinjauan Yuridis Penjatuhan Pidana Dalam Kecelakaan Lalu Lintas yang Menyebabkan Orang Lain Meninggal Dunia (Studi Pada Putusan Nomor 76/Pid.Sus/2017/PN Unr) - Prakoso, Kurnia Sandhi Dwi; Yulianis, M. Sifa’ F. (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The purpose of this study is to discuss and analyze the application of criminal law in traffic accidents that cause other people to die in Decision Number 76 / Pid.Sus / 2017 / PN Unr and discuss and analyze the judge's decision in the case of traffic accidents that cause others to die in Decision Number 76 / Pid.Sus / 2017 / PN Unr. This research is included in normative juridical research. The results showed that the application of criminal law in traffic accidents that caused other people to die in Decision Number 76/Pid.Sus/2017/PN Unr showed that the defendant Mohamad Rosul bin Alm Damsu had been legally and conclusively proven guilty of the criminal act of driving a motor vehicle because his negligence resulted in a traffic accident resulting in death and serious injury. The defendant was sentenced to imprisonment for seven months. The results also showed that the judge's decision in the case of a traffic accident that caused another person to die in Decision Number 76 / Pid.Sus / 2017 / PN Unr showed that the decision-making process carried out by the Panel of Judges was in accordance with applicable legal rules, namely based on at least two valid evidence, where the evidence used was sanski testimony, evidence, visum et repertum of Ambarawa Regional General Hospital number: 445/VER/577/2017 dated March 29, 2017 and the defendant's statement.